FORMATIVE EVALUATION CIPP MODEL FOR THE IMPROVEMENT OF THE INTEGRATED SERVICE MOBILE BY THE DEPARTMENT OF ANIMAL HUSBANDRY AND FISHERIES OF BLITAR REGENCY - Astrid Puspita Wardhani, Friztya; Siti Azizah (JCI Publisher, 2025)
This study aims to evaluate the implementation of the Integrated Service Vehicle Program organized by the Department of Animal Husbandry and Fisheries of Blitar Regency using the CIPP (Context, Input, Process, Product) evaluation model as a framework for developing improvement strategies. A descriptive qualitative approach was applied with data collected through in-depth interviews, observation, documentation, and questionnaires. The main informants consisted of program officers, while additional informants were farmers selected using the snowball sampling technique. Data were analyzed using the interactive model of Miles and Huberman with the assistance of NVivo software to facilitate thematic coding and data triangulation. The results of the study indicate that the Integrated Service Vehicle Program has generally achieved its objectives by providing animal health services, extension activities, and technical assistance to farmers in remote areas. However, several challenges remain, including limited resources, inconsistent scheduling, and insufficient public outreach. Based on the SWOT analysis, the recommended improvement strategies focus on enhancing coordination, strengthening staff capacity, utilizing information technology, and expanding service coverage. These findings are expected to contribute to improving the quality and effectiveness of the Integrated Service Vehicle Program under the Department of Animal Husbandry and Fisheries of Blitar Regency.